Differences In the Imposition of Corruption Criminal Sanctions - Siti Hardiyanti Abas (Universitas Negeri Gorontalo, 2022)
The purpose of this study was to find out whether or not the District Court's decision in decision No. 18/Pid.Sus-TPK/2020/Pn Gto and No. 09/Pid.Sus-TPK/2021/Pn Gto and the factors behind the differences in the imposition of sanctions in the two cases. The research method is normative research. Research resultverdict no. 18/Pid.Sus-TPK/2020/Pn Gto the three pieces of evidence which were one of the judge's considerations in imposing a sentence on the defendant. The fact of the trial was that the defendant had been legally proven to have committed a crime that was detrimental to the state so through the two conditions for imposing a sentence, the judge's conviction was built that the defendant was the perpetrator so that the decision was appropriate as a criminal responsibility committed by the defendant. Verdict No. 09/Pid.Sus-TPK/2021/Pn Gto because no evidence was found in the form of letters and witness statements which could prove that the defendant had committed a crime. The fact of the trial formed the judge's belief that the defendant was not proven to have committed a crime and the defendant must be acquitted of all lawsuits.